003 Detecting hypertensive heart disease: The additive value of cardiovascular magnetic resonance imaging. (5th May 2016) - Charalambos, Max; Rodrigues, Jonathan; Burchell, Amy; Dastidar, Amardeep Ghosh; Ratcliffe, Laura; Hart, Emma; Hamilton, Mark; Paton, Julian; Nightingale, Angus; Manghat, Nathan
Abstract : Introduction: International hypertension guidelines advise screening for hypertensive heart disease (HHD) to aid risk stratification. Cardiac magnetic resonance (CMR) is the current non-invasive gold-standard for assessing ventricular structure/function. We aimed to determine the additive value of CMR in hypertensives over echocardiography. Methods: 85 subjects (60% men, office systolic BP: 165 ± 28mmHg, office diastolic BP: 94 ± 14mmHg) from our tertiary hypertension clinic with preceding echo underwent 1.5T CMR. Left ventricular mass and volumes were estimated from short-axis steady-state free precession cines. LVH was defined on the basis of echo and CMR normal reference ranges. The presence and pattern of myocardial late gadolinium enhancement (LGE) was documented. Results: Overall, there was no difference in prevalence of LVH by echo compared to CMR (68% vs 66%, P = 0.746). However, there was a discrepancy between echo and CMR in 28%. Relative to CMR gold-standard, echo over-diagnosed LVH in 15% and missed LVH in 13%. The diagnostic performance of echo at detecting LVH was as follows: specificity 55%, sensitivity 80%, positive predictive value 78%, negative predictive value 59% and overall accuracy 72%. Ischaemic LGE was present in 7% of subjects and non-ischaemic LGE was present in 9%. Conclusion: Echocardiography over-diagnosed and under-diagnosed LVH in an important minority of patients. LGE tissue characterisation is unique to CMR and identified ischaemic and non-ischaemic myocardial fibrosis is an important minority of hypertensives. Our findings support an extended role of CMR in hypertension where documenting in the presence/absence of HHD may have clinical management implications.